2021
DOI: 10.1017/cjn.2021.57
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Cranioplasty Utilizing 3D Printed Molds: A Canadian Single-Center Experience

Abstract: Background: Cranioplasty is a commonly performed neurosurgical procedure used to repair defects of the cranial vault. For large defects, 3D printing allows for the creation of patient-specific synthetic cranioplasties. Although these implants provide excellent cosmetic results for patients, costs are quite high. This makes their routine use challenging in the current Canadian healthcare environment. The purpose of this study is to report our experience with a novel, cost-effective method for cranioplasty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…With these, only minimal deviations from the original surface profile and an excellent esthetic appearance can be assumed. Reports on less expensive implants manufactured with 3D-printed molds also describe very good cosmetic results, but an objective quantitative analysis, as performed in the current work by means of volumetry, cannot be found in any of these articles [ 15 , 20 , 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With these, only minimal deviations from the original surface profile and an excellent esthetic appearance can be assumed. Reports on less expensive implants manufactured with 3D-printed molds also describe very good cosmetic results, but an objective quantitative analysis, as performed in the current work by means of volumetry, cannot be found in any of these articles [ 15 , 20 , 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…This procedure seems to be particularly suitable for benign lesions and is described in some reports for sphenoorbital meningiomas [ 5 , 10 , 28 ]. However, the relatively high costs of patient-specific implants must be considered, which makes them unlikely to be affordable to a broad majority worldwide [ 15 , 20 ]. Furthermore, due to the typically several weeks required for commercial implant fabrication, this single-step procedure is not feasible for aggressive or malignant lesions, and, in addition, not an option for acute reconstruction after trauma or when intraoperative adjustment of resection margins is required.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors [ 10 , 13 , 14 , 16 , 17 ] were reported to have produced more implants of different sizes ranging from 2 [ 14 ] to 32 [ 10 ]. This needs to be taken into consideration in an eventual cost-effectiveness analysis on the use of 3D-printed implants [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors decided to print a 3D-PLA mold directly, and again, PMMA was used as a cranial prosthesis [ 152 , 153 ]. Similarly, Lannon et al used desktop 3D printers to produce a PLA-made patient-specific mold for a PMMA-made final cranial implant and reported a significant reduction in the total procedure’s expenditure [ 154 ]. None of the mentioned authors experienced any significant complications that would stand out in comparison to the standard cranioplasty methods.…”
Section: 3d Cranioplastymentioning
confidence: 99%